2013
DOI: 10.3329/bpj.v16i1.14501
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Remazol Red from Textile Waste Water Using Treated Sawdust - An Effective Way of Effluent Treatment

Abstract: Activated carbon prepared from sawdust is endeavored as adsorbent for the removal of reactive dye, namely Remazol Red (RR) from aqueous media. The adsorption of RR has been studied onto activated sawdust at various particle size, adsorbent dose, temperature and pH values. The adsorptions of the above mentioned dye were designed for the Langmuir and Freundlich Isotherms. Pseudo first and second order kinetic models were used to calculate the amount adsorbed at equilibrium (q e ). The calculated values of q e fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The flask was sealed with a rubber stopper and left in continuous agitation for 48 h at 25 °C. The pH of the solution was measured and this value was the point of zero charge (Jahan Ara, 2013).…”
Section: Point Of Zero Chargementioning
confidence: 99%
See 1 more Smart Citation
“…The flask was sealed with a rubber stopper and left in continuous agitation for 48 h at 25 °C. The pH of the solution was measured and this value was the point of zero charge (Jahan Ara, 2013).…”
Section: Point Of Zero Chargementioning
confidence: 99%
“…Adsorption is considered to be an effective method for the removal of dyes, Pharmaceutical compounds due to the ease of operation and comparable low cost of application (Pereira et al, 2003;Faria et al, 2004). At present, the most commonly used adsorbent in Pharmaceutical and textile wastewater treatment is activated carbon, which has also been studied for the dye removal (Jahan Ara, 2013). But the extensive application of activated carbon is still in difficulty due to its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…And according to Choudhury (2006), not all the models but dyeing on cellulose fiber with reactive dye generally follows Langmuir and Freundlich model of adsorption isotherm. And in recent, Ara et al (2013) studied with Remazol Red RR adsorption to activated carbon. They analyzed both Langmuir and Freundlich isotherm model and observed that the Freundlich isotherm was fitted with the adsorption behavior of Red RR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to previously reported literature, treated sawdust showed an adsorption capacity of only 8.0 mg/g for RR at pH 2.0 after a very long time of 12 h [50]. In our previous study, chitosan showed an adsorption capacity of 313.4 mg/g for RR at pH 3.0 after 30 min [43].…”
Section: Comparison Of Adsorption Performancementioning
confidence: 70%